Options for Tobacco Taxation in Afghanistan - World Bank Group (World Bank, Washington, DC, 2019)
This paper presents options for tobacco taxation to reduce tobacco consumption and increase financing for health programs in Afghanistan. Tobacco consumption is compromising the health of the Afghan population, particularly the poor. Lowering tobacco consumption would help progress towards Universal Health Coverage by reducing the tobacco-related burden of disease (mortality and morbidity). This paper presents policy options for the Government of Afghanistan to reduce tobacco consumption and improve health outcomes. Tobacco taxation could serve the dual purpose of reducing consumption and generating additional tax revenue to spend on healthcare for the poor. Increasing total taxes to 46 percent of the import price is estimated to generate USD 19.7 million of additional tax revenue per year while reducing domestic consumption of cigarettes by at least 5 percent. This paper has five sections. The first section analyzes tobacco consumption in Afghanistan by socioeconomic and demographic characteristics. The second section describes the burden of disease associated with tobacco and its effect on health at the provincial level. The third section discusses current policies of tobacco control and current practices of tobacco pricing and taxation, including a brief overview of the complex relationship between government and private stakeholders. The fourth section discusses options for tobacco taxation in Afghanistan. The final section applies a simulation model to estimate health and revenue outcomes of additional tobacco taxation.